Utilización del suero de leche bovina en la alimentación de cuyes (Cavia porcellus) - Escobar R., Felipe (2025)
In the process of transforming bovine milk into cheese, the main by-product is whey (WH), a by-product rich in highly digestible organic matter, but it becomes a contaminating agent for water and soil when discarded. It is estimated that the transformation of milk into cheese in the upper basin of the Ayacucho Region-Peru results in large volumes of WH dumped into rivers and surrounding soils. The present study aimed to evaluate the use of WH in guinea pig feeding. In total, 60 weaned male guinea pigs of 3 weeks of age and average weight of 310 g (298-340 g) were used. The guinea pigs were fed fresh forage (Medicago sativa) equivalent to 10% of body weight plus commercial concentrate ad libitum. There were 4 treatments with 3 repetitions and 5 guinea pigs housed per cage as experimental units: T1 100% drinking water (AP); T2 67% AP + 33% WH; T3 33% AP + 67% WH; T4 100% WH. During the experimental period (7 weeks) no rejection of WH was observed; on the other hand, the higher the WH level, the higher the liquid consumption (p˂0.01). The increase in body weight gain and carcass yield were similar in the four treatments (p>0.01). The consumption of SL as a substitute for water was significantly higher (p˂0.01) with a favorable effect on the feed conversion ratio (FCR).